Low Tax Jurisdictions and Preferential Regimes : Policy Gaps in Developing Economies - Pemberton, Jonathan Leigh (World Bank, Washington, DC, 2019)
This paper reviews recent international initiatives and domestic policy developments aimed at helping countries to protect their tax base against erosion by individuals and companies that allocate assets to or route income via low tax jurisdictions. The paper highlights the benefits and limitations of existing policy instruments from the perspective of capital-importing developing economies. Focusing on two common policy gaps for developing economies, options are explored for (i) introducing necessary charging provisions to ensure effective taxation of individuals, and (ii) an anti-diversion rule tailored to reflect developing economy contexts and administrative constraints. These proposals include a possible definition of excess profits in low tax jurisdictions and options for distribution keys to reallocate profits to countries where there is "real" economic substance and activity. The measures discussed could also address the diversion of profits to entities benefitting from preferential regimes in countries with high nominal tax rates.